Auditoría de gestión y su incidencia en la toma de decisiones del departamento de talento humano en la empresa Agripalban S.A., cantón Quevedo, período 2019. - Peñarrieta Carbo, Karen Pamela (2021)
The present investigative work was directed to the Authorship of Management in the department of human talent of the Company Agripalban SA, of the Canton Quevedo, in which through the investigation the analysis of the management processes and indicators that are executed in the department was carried out. Of human talent. For this, the main objective was an evaluation of the incidence of management authorship in decision-making in the human talent department of this financial entity. In addition, methodologies used in the field were used as information resources where an interview and survey were carried out for the respective data collection. Likewise, results were obtained through the implementation of the authorship phases, and the solution to each proposed objective was achieved, the first through information with an interview with the manager and head of human talent, also an evaluation of the three indicators Efficiency, Efficacy and Effectiveness, second an evaluation of the internal control was made with the COSO I method, measuring the level of confidence and risk, an analysis was used in the narrative certificates of the finding found, in the third objective it was ran a profitability survey and evaluation. In which it was determined that there is a deficiency in the processes of the human talent department and a low level of profitability was presented. With this background, it was proposed that the company integrate a new management system to measure the work performance of employees and thus improve productivity and achieve better profitability for the company. Keywords: Management Audit, Human Talent, Efficiency, Effectiveness, Economy.